The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1155/2017/9102909
|View full text |Cite
|
Sign up to set email alerts
|

Roles of miR-17-92 Cluster in Cardiovascular Development and Common Diseases

Abstract: MicroRNAs (miRNAs and miRs) are a large class of noncoding, single-stranded, small RNA molecules. The precise control of their expression is essential for keeping tissue homeostasis and normal development of organisms. Thus, unbalanced expression of miRNAs is a hallmark of many diseases. Two to dozens of miRNAs can form into a miRNA cluster, and the miR-17-92 cluster is one of them. Although firstly described as an oncogenic miRNA cluster, the miR-17-92 cluster has also been found to play critical role in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 39 publications
0
34
0
1
Order By: Relevance
“…miR‐143/145 cluster is important for vascular smooth muscle cell functions such as migration, plasticity and contractile ability (Song & Li, ). Both cardiac cell development and differentiation are regulated by miR‐17/92 cluster (Gu et al, ). miRNA clusters associated with cardiac development and regeneration include miR‐1/133a clusters (Liu et al, ).…”
Section: Significance Of Mirna Clusters In Health and Diseasementioning
confidence: 99%
“…miR‐143/145 cluster is important for vascular smooth muscle cell functions such as migration, plasticity and contractile ability (Song & Li, ). Both cardiac cell development and differentiation are regulated by miR‐17/92 cluster (Gu et al, ). miRNA clusters associated with cardiac development and regeneration include miR‐1/133a clusters (Liu et al, ).…”
Section: Significance Of Mirna Clusters In Health and Diseasementioning
confidence: 99%
“…MiRNAs participate in normal cellular physiology such as differentiation and proliferation but also in the progression of a variety of diseases by influencing gene expression in heart, lung, immune system, etc. [37]. Both miRNA biosynthesis and function have been extensively reviewed [38,39].…”
Section: Circulating Mirnas As Biomarkers In Cardiovascular Diseasesmentioning
confidence: 99%
“…In addition, a large proportion of miRNAs are expressed as clusters that are subsequently processed into individual mature molecules. It has been demonstrated that specific miRNA clusters are essential to the normal development of the cardiovascular system [37]. For example, some miRNAs clusters are important for activation of endothelial cells, post-natal neovascularization, cardiovascular development and regeneration [37,46] as well as for vascular smooth muscle cell functions such as migration, plasticity, and contractile ability [47].…”
Section: Circulating Mirnas As Biomarkers In Cardiovascular Diseasesmentioning
confidence: 99%
“…Importantly, we identified epigenetic alterations as a consequence of gestational CRD which support the phenotypes observed. The promoter region of miR17-92, required for heart and bone development (Gu et al 2017;Mohan et al 2015), was hypermethylated in the jet lag offspring, and increased expression of one of the targets of this miR cluster, P21, was increased in the hearts of the jet lag offspring. Additionally, DMRs were identified within circadian clock genes and genes involved in clock resetting, resulting in altered gene expression.…”
Section: Discussionmentioning
confidence: 98%
“…We performed gene ontology analysis using this group of differentially methylated genes and identified biological processes which are affected in the jet lag offspring (Figure 4b,c). A feature that all these processes have in common is that they are regulated by micro-RNA cluster miR17-92 (Gu et al 2017;Mendell 2008;Mohan et al 2015), which is hypermethylated in the DEL and ADV groups (Figure 4a). A graphic representation of the methylation levels in miR17 is shown in Figure S4A.…”
Section: Chronic Gestational Jet Lag Affects Heart Morphology and Funmentioning
confidence: 99%